Build a Perfume Shop Sales Web in Pontianak City - Firmansyah Harahap; Widyasari Widyasari (STMIK Pontianak, 2021)
This research is motivated by the increasing number of trade shops and services that are starting to use the E-Commerce system as an online sales medium. By using E-Commerce store information can be conveyed more quickly to customers and a wider marketing reach, so it is expected to increase product sales at perfume shops. This study uses the Visual Studio Code application as a medium for making E-Commerce websites because it has complete features and many modules. which is available for free. Here a website-based online promotion and sales media will be designed, this design and manufacture is intended to facilitate processing, sales and promotion and buyers. So that it is easier for consumers to choose the scent of perfume, without consumers having to come to the store. Promoting a product must be accompanied by an easy and attractive concept to attract consumers and the public.